Austerity urbanism: connecting strategies and tactics for participatory placemaking. Issue 4 (2nd October 2021) - Sara, Rachel; Jones, Matthew; Rice, Louis
ABSTRACT: Austerity has led to a growing interest in small-scale urban practices that engage community groups in participatory placemaking as an alternative to developing government or commercially funded parks and urban spaces. These approaches draw on bottom-up tactics to empower local community groups to take ownership of small communal spaces but are also often supported strategically by small financial grants provided by local and national governments. In this article, we draw on de Certeau's theory of strategies and tactics to explore the relationship between top-down strategies and bottom-up tactics in urban placemaking in response to the politics of austerity. We explore this process through critical analysis of our own participatory action research project to engage in the ideation and implementation of a community-run 'Pocket-Park'. We argue that the complex interplay between participatory bottom-up tactics and more formal top-down strategies provides an approach to placemaking that uniquely facilitates creative practice and allows for a resurgence in non-commercialised public placemaking. We identify a process of manoeuvres (or strategic tactics) between de Certeau's two concepts in which key participants undertake a translational process, to unlock the resources needed to support tactical placemaking.